A Preliminary Survey on Faunal Diversity of Kuldiha Wildlife Sanctuary with Special Reference to Lesser-known forms, Orissa - Das, Sunit K.; Rout, S. D.; Sahoo, D. P.; Mohanta, P.; Brahma, A. (Indian Forester, 2010)
Study was conducted to get some baseline information on faunal diversity of Kuldiha Wildlife Sanctuary of Balasore district, Orissa. Habitat surveyed includes tropical semi evergreen forest, sal tree forest, moist mix deciduous forest, roadside vegetation, water bodies and their surroundings. A total of 86 species of invertebrates, 9 species of fishes, 5 species of amphibian, 39 species of reptiles, 133 species of birds and 25 species of mammals were recorded during the study. Sloth bear and Elephant are the key species of the area. Sanctuary is a good habitat for Leopard. Other mammals have low population due to hunting and food gathering habit of tribal and loss of habitat. The presence of giant squirrel also indicates the good health of the upper canopy of the sanctuary.